PROCUREMENT AND SUPPLY CHAIN MANAGEMENT AT ROLLS ROYCE - Amanpreet; Kumar Garg, Parveen (International Journal of Psychosocial Rehabilitation, 2021)
As part of its worldwide sourcing process, Rolls-Royce evaluates each partner’s ability to meet Rolls-Royce requirements at every stage of the supply chain, from procuring raw materials and producing components to assembling the final product. Logistics nodes ranging from suppliers to manufacturers, domestic and international, work seamlessly.